Close work partnership is key - CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
Dr. Frank Rijsberman, CEO, CGIAR Consortium speaks on the importance the Consortium attaches to the #AASW6. The Forum for Agricultural Research in Africa (FARA) in collaboration with the Government of Ghana will convene the 6th Africa Agriculture Science Week from July 15-19 in Accra, a continental gathering of all stakeholders involved in African agriculture. Learn more: http://www.cgiar.org/calendar-events/ http://www.fara-africa.org/scienceweek/